Robot-assisted laparoendoscopic single site adrenalectomy: A comparison of 3 different port platforms with 3 case reports. Issue 51 (December 2017) - Kan, Hung-Cheng; Pang, See-Tong; Wu, Chun-Te; Chang, Ying-Hsu; Liu, Chung-Yi; Chuang, Cheng-Keng; Lin, Po-Hung
Abstract: Rationale: Laparoscopic adrenalectomy is currently the standard of care for adrenal lesion. Minimal invasive laparoscopic surgery such as laparoendoscopic single site surgery (LESS) and natural orifice transluminal endoscopic surgery (NOTES) have been developed to improve cosmetic outcomes and reduce postoperative pain. However, there are still some problems related to instruments and port limitation during LESS surgery. Robot-assisted laparoscopic surgery may help to overcome these problems, and port platforms selection is an important issue. Patient concerns: Three cases received robot-assisted LESS adrenalectomy due to adrenal tumor were enrolled. Blood loss, hospital stay, and analgesia injection were compared. Diagnoses: Preoperative evaluations were done in a usual manner. Benign tumors were suspect for two patients, while metastatic tumor could not be excluded for the other patient with prior malignancy history. The pathology reports were all benign adrenal cortical adenoma after operation. Interventions: Three different port platforms, Da Vinci Single-Site Surgical Platform, GelPOINT, and homemade glove port were used. Trans-peritoneal approach was used for two patients, while the other one received trans-retroperitoneal approach. The advantage and disadvantage of different port platforms were discussed. Outcomes: All patients underwent the operation smoothly without major complications or conversion to open surgery. Blood loss amount was small, hospital stay was short, and only one patient received one single dose of opioid analgesia injection after the surgery. Lessons: The main problems of LESS are the loss of a working triangle and the limitations of the instruments. Robot-assisted LESS may help surgeons overcome part of these problems. Many different port platforms are available, and based on our initial experience, we believe that the GelPoint may be a more suitable platform, for it maintains the endo-wrist function of the Da Vinci instruments, and allows the surgeon to design the position of ports freely to minimize external and internal collision.